Application of The Synesthetic Approach in A Layout Design Course - Ellis Melini (Visual Communication Design Department of Universitas Pelita Harapan, 2021)
In visual communication design education, teachers strive to help students understand how to generate ideas in whatever form of graphics they are trying to create. This paper focuses on how we apply the concept of synesthesia in a visual composition, specifically in the form of a page layout comprising both text and images. This research is done in a class of second-year students majoring in graphic design in a visual communication design bachelor program. Students are given an assignment to create a multi-column layout and incorporate the synesthesia concept in their design. The result is quite interesting, with some artworks showing what can be considered as universal synesthetic experience for the viewers. The artworks are then evaluated and considered for future classroom exercises.